Aortic perforation due to cardiac resynchronisation therapy defibrillator lead placement: Case report and medicolegal considerations. Issue 6 (16th June 2015) - Grande, Antonino M.; Fiore, Antonio; Merlano, Maurizio; Buzzi, Fabio; Mazzola, Alessandro
Abstract: A 45‐year‐old woman with dilated cardiomyopathy was admitted for the upgrade of a previously implanted pacemaker. Echocardiography showed intraventricular dyssynchrony and a low ejection fraction (0.35). Treatment with a cardiac resynchronization therapy defibrillator (CRT‐D) was selected and the device was implanted. CRT‐D interrogation revealed proper function. Following procedure termination, the patient went into cardiac arrest and died despite resuscitation attempts. An autopsy revealed that the medial aspect of the right atrium was pierced by an active lead and that the aorta had a deep lesion, 2 mm in length, on its lateral aspect. We explain the probable pathogenesis of this patient's death.